The effect of abdominal drawing-in manoeuvres and abdominal bracing techniques via telerehabilitation on lumbar repositioning error in seated sedentary participants with chronic low back pain and lumbar instability: a randomised controlled trial - Saiklang, Pongsatorn; Chatprem, Thiwaphon; Saiklang, Parvinee; Puntumetakul, Rungthip; Yeowell, Gillian (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Purpose. Lumbar stabilisation exercise (LSE) is recommended for patients with lumbar instability (LI). Two popular techniques include the abdominal drawing-in manoeuvre (ADIM) and abdominal bracing (AB). These techniques have proven their efficacy in the clinical setting; however, there is no comparable effect when they are conducted via telerehabilitation. To investigate the effects of two LSE techniques, ADIM and AB, delivered via telerehabilitation on lumbar repositioning error (LRPE), numeric rating scale, and transversus abdominis muscle performance in seated sedentary participants with chronic low back pain (CLBP) and LI.Methods. The study used a parallel-group, randomised controlled trial design. Fifty-four seated sedentary participants with CLBP and LI were randomly assigned to the AB, ADIM, or control groups. Outcome measures included LRPE, numeric rating scale, and transversus abdominis muscle performance, assessed at baseline and after 4 weeks.Results. The ADIM and AB groups showed significant improvements in LRPE and numeric rating scales after 4 weeks, while the control group improved only on the numeric rating scale. Between-group analysis revealed the ADIM group had a significantly lower LRPE compared to the other groups. Additionally, the ADIM group exhibited a significant improvement in transversus abdominis muscle performance compared to the control (p < 0.001) and AB (p < 0.001) groups after 4 weeks of treatment.Conclusions. Both techniques reduced LRPE and numeric rating scales, but the ADIM more effectively enhanced transversus abdominis muscle performance and decreased LRPE, making it a more beneficial intervention for managing LI.